Cis-Δ9-tetrahydrocannabinolic acid occurrence in Cannabis sativa L - Tolomeo, Francesco; Russo, Fabiana; Kaczorova, Dominika; Vandelli, Maria Angela; Biagini, Giuseppe; Laganà, Aldo; Capriotti, Anna Laura; Paris, Roberta; Fulvio, Flavia; Carbone, Luigi; Perrone, Elisabetta; Gigli, Giuseppe; et al. (Journal of pharmaceutical and biomedical analysis, 2022)
Cannabidiolic acid (CBDA) and trans-Δ9-tetrahydrocannabinolic acid (trans-Δ9-THCA) are known to be the major phytocannabinoids in Cannabis sativa L., along with their decarboxylated derivatives cannabidiol (CBD) and trans-Δ9-tetrahydrocannabinol (trans-Δ9-THC). The cis isomer of Δ9-THC has been recently identified, characterized and quantified in several Cannabis sativa varieties, which had been heated (decarboxylated) before the analysis. Since decarboxylation alters the original phytocannabinoids composition of the plant, this work reports the identification and characterization of the carboxylated precursor cis-Δ9-THCA. The compound was also synthesized and used as analytical standard for the development and validation of a liquid chromatography coupled to high resolution mass spectrometry-based method for its quantification in ten Cannabis sativa L. samples from different chemotypes. The highest concentrations of cis-Δ9-THCA were found in CBD-rich varieties, lower levels were observed in cannabigerol (CBG)-rich varieties (chemotype IV) and in those varieties with a balanced level of both CBD and THC (chemotype III), while its levels were not detectable in cannabichromene (CBC)-rich varieties (chemotype VI). The presence of the cis isomer of THC and THCA raises the question on whether to include or not this species in the calculation of the total amount of THC to classify a cannabis variety as a drug-type or a fiber-type (hemp).
Keywords: Cis-Δ(9)-tetrahydrocannabinol; Cannabinoids; Chromatography, High Pressure Liquid; Cannabidiol; kanabidiol; tetrahydrokanabinol; Cannabis; Cannabis sativa; HPLC-HRMS; Cis-Δ(9)-tetrahydrocannabinolic acid; Dronabinol; vysokoúčinná kapalinová chromatografie